Policy implications of land use changes in the uplands of northern Lao PDR - Douangsavanh, L.; Laddavong, P.; Bouahom, B.; Castella, J.C. (2011)
The 2000s decade has seen a lot of changes in the northern uplands of Lao PDR that where driven by three main drivers or agents of change: government policies, foreign private investors and development assistance led by bilateral or multilateral organizations or international NGOs. These three spheres of influence are intimately connected and constantly interacting as they depend on each other’s to reach their goals or fulfill their mandate. They have brought new rules, opportunities, and also risks to rural populations who had to cope with very rapid changes. This paper explores possible adaptations to existing policies that would facilitate a smoother agrarian transition from subsistence to commercial agriculture; i.e. avoiding external chocks and maintaining the resilience of rural communities. Indeed, farmers capacity to adapt to changes and to adopt technical and institutional innovations should be harnessed by providing a supportive policy environment.